TUMPANGSARI PADI-RUMPUT DAN APLIKASI ASAP CAIR TEMPURUNG KELAPA TERHADAP PERTUMBUHAN, FISIOLOGI DAN HASIL PADI GOGO - Ahadiyat Yugi R; Sajuri Sajuri; Darjanto Darjanto (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2017)
The objective of this research is to know the effect of intercropping paddy-grass and Applications of coconut shell wood vinegar on plant growth, physiologycal characters and yield of upland rice. Research conducted at the villageof Cendana, District of Kutasari, Purbalingga in March, 2015 to August, 2015. The field experiment with split plot design with three replications. The main plot, was carried wit paddy-grass intercropped consisting of: rice monoculture, upland rice- elephant grass and upland rice-lemongrass. Sub plot, a dose of coconut shel wood vinegarl i.e. without coconut shell wood vinegar, a concentration of 1: 200 and a concentration of 1: 400. The variables observed were plant height, number of leaves, leaf area, number of tillers, weight of dry shoot, the weight of the dried root, the growth rate of plants, relative growth rate, net assimilation rate, the contain of proline, contain chlorophyll, panicle length, number of panicles, number of filled grain, grain meight per hill, grain weight of 1000 seeds, grain weight / ha, harvest index, soil water content, the intensity of the damage and the value of equality of results. Intercropping rice-grass and coconut shell liquid smoke applications have not been able to improve the character of the growth, physiology and yield.